Evaluating Claims of Early Human Occupation at Chiquihuite Cave, Mexico. (2nd January 2022) - Chatters, James C.; Potter, Ben A.; Prentiss, Anna Marie; Fiedel, Stuart J.; Haynes, Gary; Kelly, Robert L.; Kilby, J. David; Lanoë, François; Holland-Lulewicz, Jacob; Miller, D. Shane; Morrow, Juliet E.; Perri, Angela R.; et al.
ABSTRACT: Archaeologists working in Mexico recently claimed evidence for pre-Last Glacial Maximum human occupation in the Americas, based on lithic items excavated from Chiquihuite Cave, Zacatecas. Although they provide extensive array of ancillary studies of the cave's chronostratigraphic and paleoenvironmental record, the data they present do not support their central argument, that these lithic items are anthropogenic and represent a unique lithic industry produced by early human occupants. They give limited consideration to the most plausible alternative explanation: that the assemblage is a product of natural processes of disintegration, roof fall, and mass movement of the cave fill, and thus the lithic materials are best explained as geofacts. We assess the evidence by considering the alternative hypotheses (1) that the observed phenomena are artifacts or (2) that they result from natural processes. We conclude that hypothesis 2 is more strongly supported and that Chiquihuite Cave does not represent evidence for the earliest Americans.